A novel 2 bp deletion variant in Ovine-DRB1 gene is associated with increased Visna/maedi susceptibility in Turkish sheep - Yalçın Yaman (Nature Portfolio, 2021)
Abstract Visna/maedi (VM) is a multisystemic lentivirus infection of sheep that affecting sheep industry across the globe. TMEM154 gene has been identified to be a major VM-associated host gene, nevertheless, a recent study showed that the frequency of the VM-resistant TMEM154 haplotypes was very low or absent in indigenous sheep. Thus, the present study was designed to determine other possible co-receptors associated with VM. For this purpose, DRB1 gene, which is renowned for its role in host immune response against various diseases was targeted. A total number of 151 case–control matched pairs were constructed from 2266 serologically tested sheep. A broad range of DRB1 haplotype diversity was detected by sequence-based genotyping. Moreover, a novel 2 bp deletion (del) in the DRB1 intron 1 was identified. For the final statistic, the sheep carrying VM-resistant TMEM154 diplotypes were removed and a McNemar’s test with a matched pairs experimental design was conducted. Consequently, it was identified for the first time that the 2 bp del variant is a genetic risk factor for VM (p value 0.002; chi-square 8.31; odds ratio 2.9; statistical power 0.90) in the dominant model. Thus, negative selection for 2 bp del variant could decrease VM infection risk in Turkish sheep.